اختصاصات مجلس الدولة وفقا لتعديلات قانون الإجراءات المدنية والإدارية لسنة 2022 - بلحوت، عفاف; بن ساسي، أمينة (جامعة الوادي University of El Oued, 2024)
تضمنت تعديلات 2022 على قانون الإجراءات المدنية والإدارية في الجزائر تعديلات هامة تتعلق بمجلس الدولة واختصاصاته القضائية، حيث تم تحسين وتعزيز دور مجلس الدولة كهيئة عليا للقضاء الإداري مع توسيع اختصاصاته لضمان عدالة وفعالية أكبر لنظر في النزاعات الإدارية، وركزت كذلك على تسريع وتيرة الفصل في القضايا من خلال تحسين المواعيد والإجراءات، مما يقلل تراكم القضائي وتحسين من سرعة وشفافية إجراءات التقاضي الإداري والرقابة على مشروعية القرارات الإدارية للإختصاصات القضائية التي يمارسها مجلس الدولة لبناء دولة القانون، حيث يمارس مهامه كقاضي قانون من خلال الفصل في الطعن بالنقض وهذا ما جعل له المشرع الجزائري كقاضي ثاني درجة بالنسبة للأحكام الإبتدائية الصادرة عن المحاكم الادارية وكما جعل له جهة أولى وآخر درجة بالنسبة للقرارت الصادرة عن الإدارة المركزية، ولقد حافظ مجلس الدولة على اختصاصه الاستئنافي بصفة استثنائية فقط في القرارات القضائية الصادرة عن المحكمة الإدارية الاستئنافية بالعاصمة عندما تفصل كدرجة أولى في الدعاوى المتعلقة بالقرارات الإدارية الصادرة عن السلطات المركزية والهيئات العمومية الوطنية والمنظمات المهنية الوطنية. The 2022 amendments to the Code of Civil and Administrative Procedure in Algeria included important amendments related to the State Council and its judicial powers, as the role of the State Council was improved and strengthened as a supreme body for the administrative judiciary while expanding its powers to ensure greater fairness and effectiveness in considering administrative disputes. It also focused on accelerating the pace of adjudicating cases from By improving appointments and procedures, which reduces judicial backlog, improves the speed and transparency of administrative litigation procedures, and monitors the legality of administrative decisions for the judicial powers exercised by the Council of State to build the state of law, where he exercises his duties as a judge of law by deciding on appeals in cassation, and this is what the Algerian legislator made him a second judge. One degree in relation to primary rulings issued by administrative courts. It also has a first and last degree in relation to decisions issued by the central administration. The State Council has maintained its appellate jurisdiction on an exceptional basis only in judicial decisions issued by the Administrative Court of Appeal in the capital when it decides as a first degree in cases related to administrative decisions. Issued by central authorities, national public bodies and national professional organizations
قانون اداري